2020
DOI: 10.1108/ajems-01-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetry effect of oil price changes on inflation, and the welfare implication for Ghana

Abstract: PurposeHigh inflation levels remain a challenge in macroeconomic stabilization policies among developing economies. Oil price is identified as an important driver of inflation. In the wake of high and unstable international oil prices, the question regarding the relationship between inflation and crude oil prices, and its implication for economic welfare has become a fundamental empirical issue.Design/methodology/approachThis question is explored by estimating a non-linear autoregressive distribution lags (NAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…The results of this study provide empirical evidence that there are asymmetrical effects on the movement of world energy prices, especially crude oil, when they rise and fall on CPI inflation in Indonesia. The finding of an asymmetrically positive effect of oil prices on inflation confirms the results of research by Donayre and Wilmot (2016), Bala and Chin (2018), Sek (2019), Bawa et al (2020), Babuga and Naseem (2021), Ayisi (2021), Sarmah andBal (2021), andNie (2023). Specifically, however, these findings differ from those by Babuga and Naseem (2021) and Nie (2023), that increases in oil prices have a more significant effect on inflation than decreases.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of this study provide empirical evidence that there are asymmetrical effects on the movement of world energy prices, especially crude oil, when they rise and fall on CPI inflation in Indonesia. The finding of an asymmetrically positive effect of oil prices on inflation confirms the results of research by Donayre and Wilmot (2016), Bala and Chin (2018), Sek (2019), Bawa et al (2020), Babuga and Naseem (2021), Ayisi (2021), Sarmah andBal (2021), andNie (2023). Specifically, however, these findings differ from those by Babuga and Naseem (2021) and Nie (2023), that increases in oil prices have a more significant effect on inflation than decreases.…”
Section: Discussionsupporting
confidence: 79%
“…Meanwhile, there is no evidence of the effect of changes in the exchange rate on changes in the CPI in the short run. Empirical studies related to the asymmetric effect of world oil prices on inflation only found evidence for long-run effects but not for short-run effects, in line with findings by Ayisi (2021). In general, the behavior of changes in energy prices and exchange rates tends to fluctuate so that it does not affect inflation according to theoretical expectations.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The motivation for studying the influence of global commodity prices on inflation in a developing country like Ghana stems from the need to understand the factors driving inflation and exchange rates in the country. Although several studies have shown that commodity, prices, such as oil, cocoa, and petroleum products, can have a significant impact on inflation [17][18], this present study seeks to study both the influence on inflation and exchange rates interactions. In Ghana, fluctuations in these commodity prices can lead to changes in the overall price level, affecting the cost of living for the population.…”
Section: Research Gaps Motivation and Contribution Of The Researchmentioning
confidence: 99%